2019
DOI: 10.1111/jch.13647
|View full text |Cite
|
Sign up to set email alerts
|

Self‐blood pressure monitoring is associated with improved awareness, adherence, and attainment of target blood pressure goals: Prospective observational study of 7751 patients

Abstract: A large-scale, cross-sectional study incorporating data from various countries around the world, including both low-and high-income subjects, showed that the prevalence of hypertension (HTN) was 40.8% in 142 042 participants, but only 46.5% were aware of the diagnosis criteria, and 32.5% had controlled blood pressure (BP), despite the high rate (87.5%) of pharmaceutical treatment. 1 Low BP control could be attributed to poor medication adherence and patients' ignorance on the importance of HTN, as well as ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In the current issue of Journal of Clinical Hypertension , Jo and coll reported the results of an observational prospective study, assessing the impact of a 3‐month self‐BP monitoring program on BP control, compliance to treatment, and awareness of hypertension. The study population consisted of a large cohort of 7751 hypertensive patients attending outpatient clinics of private and university hospital in Korea …”
Section: Meta‐analyses Investigating the Effect Of Self‐blood Pressurmentioning
confidence: 99%
See 4 more Smart Citations
“…In the current issue of Journal of Clinical Hypertension , Jo and coll reported the results of an observational prospective study, assessing the impact of a 3‐month self‐BP monitoring program on BP control, compliance to treatment, and awareness of hypertension. The study population consisted of a large cohort of 7751 hypertensive patients attending outpatient clinics of private and university hospital in Korea …”
Section: Meta‐analyses Investigating the Effect Of Self‐blood Pressurmentioning
confidence: 99%
“…The authors found that after the 3‐month period of SBPM, BP significantly decreased, the number of patients with controlled BP increased, and adherence to drug therapy and patients’ perception of BP improved …”
Section: Meta‐analyses Investigating the Effect Of Self‐blood Pressurmentioning
confidence: 99%
See 3 more Smart Citations